Efficacy and Safety of Different Doses of Urico-Lowering Agents in The Treatment of Gout with Hyperuricemia: A Systematic Review and Network Meta-Analysis - Wen Jie; Wang Yongyan; Li Jialin; Zhang Yiying; Shi Yan; Li Xingzhou; Sun Xuewei (BIO Web of Conferences)
Objectives: To systematically evaluate the efficacy and safety of different doses of uric acid- lowering drugs (allopurinol, febuxostat, and benzbromarone) in patients with gout with hyperuricemia by using the method of reticulated Meta-analysis. Methods: Published clinical randomized controlled trials (RCTs) on the efficacy and safety of febuxostat, allopurinol, and benzbromarone in the treatment of gout with hyperuricemia were searched. Results: A total of 17 papers randomized controlled publications met the criteria were included, including 3461 patients (The actual number of people completed 2797) patients actually completed. Mesh meta-analysis showed that 120 mg of febuxostat had better clinical efficacy than other drugs (cumulative probability ranking curve (SUCRA) was 98.5%); 120 mg of febuxostat showed better efficacy in terms of safety than other drugs (cumulative probability ranking curve (SUCRA) was 72.0%). Conclusion: The efficacy and safety of 120 mg febuxostat in the treatment of gout with hyperuricemia were superior to other uric acid lowering drugs. This review recommended 120 mg of febuxostat for the treatment of patients with gout with hyperuricemia.